A 20-year review of National Health Service Resolution Occupational Therapy litigation data in the United Kingdom. (March 2022) - Soderberg Garcia, Veronica; Heritage, Sara; Winter, Rebecca Ellen; Furness, Pamela; Wong, Ken
As with any other healthcare professional in today's medicolegal climate, the Occupational Therapist is at a risk of litigious claims being made against them. Through a Freedom of Information request, litigation claims data between 2000 and 2020 against National Health Service Occupational Therapists in the United Kingdom were obtained from National Health Service (NHS) Resolution. We perform a descriptive analysis of the results and review the literature around litigation involving Occupational Therapists. 79 claims were registered over this period, of which 37 were settled with damages. The most common primary injury for successful claims was fracture. The most common primary causes for successful claims were equipment malfunction and lack of assistance/care. The total cost for successful claims was £1, 655, 771. These data demonstrate that Occupational Therapy is a trusted profession, with a low rate of claims. We frame these findings in context and discuss lessons behind the data.